Implementasi Budaya Madrasah Dalam Perspektif Pendidikan Karakter - Khairul Ihsan Arif; Ansar Ansar; Muh Ardiansyah (Universitas Negeri Makassar, 2022)
This research examines the implementation of madrasah culture from the perspective of character education in Madrasah through structural and cultural approaches. This study aims to discover and describe the performance of madrasa culture from the perspective of character education. This research approach is qualitative with a phenomenological type of research. This research was carried out at madrasah Ibtidaiyah Negeri 3 Luwu. The data sources in this study are the head of the madrasa, the curriculum coordinator, and the teacher—data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation, and concluding. I was checking the validity of the data using triangulation techniques. The results showed that the values of character education are integrated from various structural aspects. The use of structural-functional elements in organizing character education is an effort to supervise and guide the development of madrasah culture, in this case, related to the internalization of character education values towards madrasah residents, especially on the object of education, namely students. The implementation of madrasah culture in the perspective of character education through a cultural approach which includes the behavior of madrasah residents, traditions, daily habits, and cultural symbols, can also be said to be in line with the formulation of the vision, mission, and goals of the madrasa or with the madrasah's efforts in building a positive culture. The behavior of madrasah residents has been applied to the values of character education cultivated due to integration into every daily activity and tradition of madrasah residents through habituation efforts. In addition, madrasah culture in the perspective of character education is also found in cultural results, which become symbols in the form of the arrangement of buildings and classrooms and the uniform clothes of madrasah residents.